MAKING SENSE OF BOKO HARAM AND SUICIDE MISSIONS IN NIGERIA - Obaro, Ogaga Ayemo (European Scientific Journal, ESJ, 2013)
﻿This article attempts to highlight various motivating factors which contribute to increased incidence of suicide missions in Nigeria and world-wide. Boko Haram, the Islamic religious sect, whose name means "Western education is sacrilege" in the Hausa language of Nigeria’s north, has been waging an increasingly bloody fight against the nation’s Federal government and some Northern States governments. Boko Haram has targeted Nigeria’s police, rival clerics, politicians, and public institutions with increasing violence since 2009. Some experts say the group should primarily be seen as leading an armed revolt against the government’s entrenched corruption, abusive security forces, strife between the disaffected Muslim north and Christian south, and widening regional economic disparity in an already impoverished country. The heart-wrenching and horrible daily accounts of suicide bombings rarely reveal the underlying causes or the bombers’ motivations. But without understanding these motivations and addressing them, it would appear that governments or organizations that seek to end suicide bombings are likely to be disappointed. However, in order to understand this complex phenomenon it is important to consider the contextual factors. Boko Haram’s suspected bombing of a United Nation’s building in Abuja in August 2011 and its ties to regional terror groups may signal a new trajectory and spark a stronger international response that makes it harder to address the north’s alienation.